Analisis Penggunaan Pasir Pantai Pondok Permai Di Kecamatan Pantai Cermin Kabupaten Serdang Berdagai Sebagai Agregat Halus Terhadap Kuat Tekanan Beton (Penelitian) - Muhammad Ridho Maulana; Darlina Tanjung; Muhammad Husni Malik Hasibuan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Research on the use of beach sand as a fine aggregate in concrete is due to the abundance of beach sand in the area. This research was carried out to analyze sand and find out how much compressive strength is produced when sand is treated without being washed with sand that is treated with washing, so that from this research the local community will know and can use it as a building material. The sand used is Pondok Permai Beach Sand, Pantai Cermin District, Serdang Bedagai Regency. The planned compressive strength of the concrete is 21.7 Mpa with 40 cylindrical test objects. Tests for compressive strength of samples were carried out at ages 7, 4, 21 and 28 days and each treatment was given 5 concrete samples. This research only focuses on beach sand concrete. The analysis results show that this beach sand is included in zone IV sand, namely sand with fine grains. The average compressive strength test results of concrete for sand not treated with washing and treated with washing at age 7 were the same, namely 16.22 Mpa. For compressive strength aged 14 days, concrete with sand that was not treated with washing produced a compressive strength of 15.58 Mpa, while concrete with sand that was treated with washing reached 17.44 Mpa. For compressive strength aged 21 days, concrete with sand that was not treated with washing produced a compressive strength of 16.10 Mpa, while concrete with sand that was treated with washing produced a compressive strength of 18.55 Mpa. In the compressive strength test aged 28 days, concrete with sand that was not treated with washing produced a compressive strength of 17.33 Mpa, while concrete with sand that was treated with washing produced a compressive strength of 19.55 Mpa. From the results of this research, the researchers concluded that the fineness of sand influences the compressive strength of concrete and washed sand can increase the compressive strength of concrete.